Diagnosis of disseminated coccidioidomycosis in pregnancy through placental pathology: A case report - Adrian L. Hernandez Lopez; Mon-Lai Cheung; Michael J. Fassett (Elsevier, 2022)
There are more than 150,000 new cases of coccidioidomycosis annually in the United States and the incidence is increasing. Although the majority of cases result in mild or no symptoms, pregnancy is a risk factor for complicated and disseminated disease. Overall, coccidioidomycosis is rare in pregnancy and there have been few reports in the literature of dissemination into the placenta. This report describes a 31-year-old primigravida with coccidioidomycosis diagnosed by placental examination. In retrospect, she had mild symptoms in the antepartum period but otherwise had no immediate complications due to the infection apart from the adhesive pelvic disease. The clinician should have a high index of suspicion for coccidioidomycosis in a pregnant woman presenting with a persistent respiratory illness who resides in, or who has recently recent travelled to, an endemic area. Additionally, a diagnosis of disseminated coccidioidomycosis should be considered for a woman with adhesive pelvic disease residing in an endemic region and one should consider microscopic placental examination if these findings are noted at cesarean delivery.